Regime durability and foreign direct investment – growth nexus in developing countries - Ayub, Muhammad; W. N., W. Azman Saini; N. A., M. Naseem; Mazlan, Nur Syazwani; Laila, Nisful (Universiti Putra Malaysia, 2020)
This study examines the role of regime durability in moderating the economic growtheffect of FDI inflows in 67 developing countries over the 1984-2016 period. The results based on the generalized method-of-moments panel estimation technique reveal that countries with durable regime benefit more from FDI inflows. The empirical results are robust to two alternative indicators of regime durability and FDI. The finding is consistent with the growing view that FDI spillovers depends on the capacity of host countries to absorb and internalize new technology associated with FDI inflows. In this respect, policymakers should weigh the cost of policies aimed at attracting FDI versus those that seek to improve regime durability.